2014
DOI: 10.1016/j.virol.2014.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The NS5A-binding heat shock proteins HSC70 and HSP70 play distinct roles in the hepatitis C viral life cycle

Abstract: We previously identified HSP70 and HSC70 in complex with NS5A in a proteomic screen. Here, coimmunoprecipitation studies confirmed NS5A/HSC70 complex formation during infection, and immunofluorescence studies showed NS5A and HSC70 to colocalize. Unlike HSP70, HSC70 knockdown did not decrease viral protein levels. Rather, intracellular infectious virion assembly was significantly impaired by HSC70 knockdown. We also discovered that both HSC70 nucleotide binding and substrate binding domains directly bind NS5A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…We had previously reported that Hsc70 and Hsp70 play distinct roles in this process [13], with Hsp70 regulating NS5A-augmented IRES-mediated translation of the viral genome [12,13] and Hsc70 being involved in intracellular infectious virion assembly [13]. The inhibitors used in this study bind to both Hsc70 and Hsp70, so we used them to explore which chaperone role might be most critical in viral processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously reported that Hsc70 and Hsp70 play distinct roles in this process [13], with Hsp70 regulating NS5A-augmented IRES-mediated translation of the viral genome [12,13] and Hsc70 being involved in intracellular infectious virion assembly [13]. The inhibitors used in this study bind to both Hsc70 and Hsp70, so we used them to explore which chaperone role might be most critical in viral processing.…”
Section: Discussionmentioning
confidence: 99%
“…Hsc70, Hsp70 and their NBDs and SBDs were expressed and purified as described previously [13]. Briefly, protein expression was induced with 1 mM isopropyl β-D-1-thiogalactopyranoside (IPTG) in BL21(DE3) Escherichia coli cells with shaking at 250 rpm for 5 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The Hsp70 chaperone family and cochaperones might also be involved in replication of Dengue virus, Hepatitis C virus, Red clover necrotic mosaic virus, Sindbis virus, BMV, ToMV, Turnip mosaic virus, Rabies virus, and Borna disease virus (2,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67). Hsp70 functions by an ATP hydrolysis-driven conformational change that regulates its substrate binding and release.…”
Section: Discussionmentioning
confidence: 99%
“…These and our current results indicate that the NS5A/HSP70 interaction is critical for viral proliferation. Recently, we also analyzed the binding of heat shock cognate protein (HSC) 70 with NS5A and found that NS5A and HSC70 directly bind each other as well (Khachatoorian et al, 2014). Nonetheless, our data as well as another report indicated that HSC70 is involved in infectious virion assembly rather than IRES-mediated translation (Khachatoorian et al, 2014; Parent et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we also analyzed the binding of heat shock cognate protein (HSC) 70 with NS5A and found that NS5A and HSC70 directly bind each other as well (Khachatoorian et al, 2014). Nonetheless, our data as well as another report indicated that HSC70 is involved in infectious virion assembly rather than IRES-mediated translation (Khachatoorian et al, 2014; Parent et al, 2009). We also showed that the compensatory upregulation of HSP70 due to knockdown of HSC70 fails to improve infectious virion assembly and that simultaneous knockdown of HSP70 and HSC70 leads to a similar decrease in viral translation as knockdown of HSP70 alone further supporting the distinct roles that HSP70 and HSC70 play in the viral life cycle.…”
Section: Discussionmentioning
confidence: 99%